Biologically Inspired Large-Scale Simulation of Tree Growth - Tomasson, Rasmus (My University, 2022)
This thesis has explored solutions for large scale biologically inspired simulation of tree growth. From previous works a growth engine was adapted and implemented utilizing the parellization of graphics programming in order to simulate and visualize tree growth on a large scale. The implemented algorithm Incorporated three main biological aspects: a light evaluation method, a branch thickness estimate and a energy distribution formula. The implemented method was evaluated in terms of rendering and simulation time and it was measured, on relatively old hardware, to be able to handle simulation of up to eight million branches in a few milliseconds as well as rendering of up to fifty thousand branches within in reasonable frame rates for real time interactive applications. With improvements in terms of performance and rendering, as well as further investigation of biological features to incorporate, the method could arguably be developed into a system capable of simulating and visualizing tree growth on a large scale, with potential use cases in video games and other interactive real time applications
Keywords: Computer science; engineering; project; thesis; Computer Graphics; Visualization; Simulation